School Principals’ Opinions About Level of their Entrepreneurship - Köybaşi, Fatma; Celal Teyyar Uğurlu (European Journal of Social Science Education and Research, 2017)
The aim of the research is to find out that how they evaluate level of entrepreneurship and what sort of individual and environmental problems during they improve their sufficiency of entrepreneurship. The qualitative research’s study group is composed of 20 principals in center of Kocaeli in 2014-2015 years. Inverse sampling technical is used. The data is collected semi-structured interview. The data is analyzed by descriptive analysis. One of the results is that the most of school principals who have got high level of entrepreneurship (f=7) utter their entrepreneurship’s level link to such as diversity, innovation, activity and performance. Half of the school principals who have got low level of entrepreneurship utter their level link to lag behind with developing world. Principals who have high level of entrepreneurship (f=5) have problems about over responsibilities of individual life during improving their sufficiency of entrepreneurship. As well as, the principals have problems such as lack of communication and motivation. In view of environmental conditions, all of participants have problems about improving their sufficiency of entrepreneurship such as work ethic and value conflict and different beliefs, bureaucracy and resource copetition. In parallel with the results, there are various suggestions.
Keywords: entrepreneur; entrepreneurship; sufficiency of entrepreneurship; school principal.